2020
DOI: 10.1002/marc.202000614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copolymer Structure on Rare‐Earth‐Element Chelation Thermodynamics

Abstract: Rare‐earth elements (REEs) are crucial to modern technology, leading to a high demand for materials capable of REE extraction and purification. Metal‐chelating polymers (e.g., polycarboxylic acids, polyamines, and others) are particularly useful in these applications due to their synthetic accessibility and high selectivity. Copolymers with varied mole fractions of acrylic acid and methyl acrylate are synthesized and isothermal titration calorimetry (ITC) to measure the thermodynamics of REE binding for each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
3
13
1
Order By: Relevance
“…Each polymer–REE interaction was endothermic, and we observed relatively large values for |− T Δ S| . These entropy–driven interactions are largely the result of releasing bound water molecules surrounding the polymer and REE ion, consistent with previous observations in both polymer–metal and protein–metal binding thermodynamics. , Interestingly, we observed larger |Δ H | and |− T Δ S | values for the more isotactic PMAAs (Figures and A,B), with only slight variations in Δ G across the series.…”
Section: Resultssupporting
confidence: 91%
“…Each polymer–REE interaction was endothermic, and we observed relatively large values for |− T Δ S| . These entropy–driven interactions are largely the result of releasing bound water molecules surrounding the polymer and REE ion, consistent with previous observations in both polymer–metal and protein–metal binding thermodynamics. , Interestingly, we observed larger |Δ H | and |− T Δ S | values for the more isotactic PMAAs (Figures and A,B), with only slight variations in Δ G across the series.…”
Section: Resultssupporting
confidence: 91%
“…The thermodynamic profiles at these different ionic strengths ( Figure ) are consistent with our previous work [ 31–33 ] and other studies on polyelectrolyte binding, [ 44,45,54–57 ] showing an entropically favored binding interaction, presumably driven by the release of bound water molecules. As expected, the Gibbs free energy (ΔG) varies consistently with the binding affinity.…”
Section: Resultssupporting
confidence: 91%
“…We used Eu 3+ as a representative lanthanide ion to study polymer-metal binding, having previously observed similar binding thermodynamics across a subset of lanthanide ions with poly(acrylic acid). 9 We conducted isothermal titration calorimetry (ITC) experiments by titrating small aliquots of a Eu 3+ solution into each polymer solution (pH 5 NaOAc-HOAc buffer) (Fig. S9-S13, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] To probe these complexities, the thermodynamics (DG, DH, and DS) of the polymer-metal interaction have been studied: Binding is entropy driven, suggesting the critical role of water in REE chelation. 8,9 However, the intricate interactions among metal, polymer, and water make designing effective metalchelating materials a challenge. 10,11 Thus, understanding and ultimately controlling these interactions will enable more efficient and selective REE-extracting materials.…”
Section: Introductionmentioning
confidence: 99%